The topics in the field of education and upbringing in Sociološki pregled / Sociological review - Vasilijević, Danijela N.; Bojović, Žana; Mihajlovic, Tatjana (Sociološki pregled, 2018)
Tere are several segments signifcant for the sociology of education in the historical genesis of ideas, starting from the fact that education had power in the society until the review of the quality of education. It is possible to ilustrate the genesis of updating the sociology of education in our professional and scientifc periodicals on the analysis of the journal Sociološki pregled/ Sociological Review. Te authors whish to examine the representation of content from the feld of education, as well as the character, extensity and intensity of content in Sociološki pregled/ Sociological Review from the frst edition in 1938 until today. Research retrospective of scientifc and professional papers (766 bibliographic references) shows that updating and interpretation of educational topics usually participates with construction of sociology as the course, the establishment and development of sociology of education, but also the ideological and political context and its inﬂuence on the educational system as a whole.